PENGARUH PENGETAHUAN PERPAJAKAN, NASIONALISME, DAN KEPERCAYAAN PADA PEMERINTAH TERHADAP KEPATUHAN WPOP - Setiady, Mila Aprilia; Budyastuti, Triyani (Politeknik Bisnis Indonesia, 2025)
This research aims to analyze the influence of Tax Knowledge, Nationalism, and Trust in the Government on Individual Taxpayer Compliance registered at KPP Pratama Kalideres. This research employs a quantitative approach using the Partial Least Square - Structural Equation Modeling (PLS-SEM) technique through SmartPLS 4.0 software. The sample consists of 100 respondents selected using purposive sampling. The results indicate that tax knowledge and nationalism have a positive and significant effect on taxpayer compliance, whereas trust in the government does not show a significant effect. These findings suggest that knowledge and nationalist attitudes are more dominant factors than institutional trust in influencing tax compliance behavior.